PENAPISAN KHAMIR SELULOLITIK CRYPTOCOCCUS SP. YANG DIISOLASI DARI TANAH KEBUN BIOLOGI WAMENA, JAYA WIJAYA, PROPINSI PAPUA - Kanti, Atit (Jurnal Biologi Udayana; Vol XI, No 1, 2007)
Cryptococcus sp. was isolated from Kebun Biologi Wamena, Papua. The isolate was able to grow in media with carboxymethyl cellulose as a sole carbon source implying that isolate produced 1-3 ? endo-glucanase. To study the effect of glucose and osmotic pressure, 0.1 % glucose and 0.1 % NaCl were amended into the medium containing CMC. Glucose significantly affected cellulolytic activity and biomass synthesis. At the beginning of cell cultivation glucose augmentation appear to slightly inhibit enzyme activity. Sodium chloride also significantly affected cellulolytic activity. Profile of pH varied dependent on cultivation media. Maximum growth of biomass was achieved after glucose addition, indicating that glucose stimulated cell growth.
Keywords: Cryptococccus, cellulolytic, soil and Papua